44 Scotland Street - McCall Smith, Alexander, 1948-; Mackenzie, Robert Ian. (Prince Frederick, Md. : Recorded Books, 2005)
When Pat rents a room in Edinburgh, she acquires some interesting neighbors--including a pushy Stockbridge mother and her talented, sax-playing, five-year-old son. Her job at an art gallery hardly keeps her busy until she suspects one painting in the collection may be an undiscovered work by a Scottish master.
Compact discs.
Unabridged.
Read by Robert Ian Mackenzie.
Keywords: Young women -- Fiction; Art galleries, Commercial -- Employees -- Fiction; Apartment houses -- Fiction; Roommates -- Fiction; Edinburgh (Scotland) -- Fiction; Audiobooks; Humorous fiction; Bildungsromans